The introduction of an international model to reduce injuries in Rugby Union in South Africa - Brown, J (South African Journal of Sports Medicine, 2011)
Regular participation in physical exercise or sport is popular due to the numerous health benefits it offers to the individual.1 However, these potential benefits need to be offset against the magnitude of risk of injury that participating in the activity may present to the individual. The risk/benefit ratio varies depending on the type of activity.1 In terms of major male-dominated sports, Rugby Union presents a high risk of overall injury to the player – greater than that of cricket, soccer or even ice hockey.2 The high incidence of injury in rugby is related to the nature of the game – a field-based team sport that involves multiple contact situations over the 80 minutes of play.3 Considering the popularity of the sport, with an estimated 92 countries participating worldwide, this injury risk presents a significant global issue.3 From the inception of the game of Rugby Union, which is speculated to have been between the start of the 1600s and the mid 1800s, the game has been regarded as a violent sport and the formation of the Rugby Football Union in 1871 was necessitated, in part, by the need for laws to reduce this violence.